Pemasaran Asuransi Dalam Islam - Yeni Aprilinda; Nuri Aslami (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2022)
Sharia marketing is a business discipline that directs the process of creating, offering, and changing value from an initiator to its stakeholders, in the whole process in accordance with Islamic sharia values. So with sharia marketing, the whole process must avoid things that are contrary to Islamic principles. And as long as this business process can be guaranteed or there is no deviation from sharia principles, then any transaction in marketing can be allowed. The rationale is how insurance marketing activities can be carried out based on Islamic values, which express responsive, responsible marketing, and always provide satisfaction to customers and benefit the company. Keywords: Sharia Marketing, Sharia Life Insurance